2012
DOI: 10.1242/jeb.074799
|View full text |Cite
|
Sign up to set email alerts
|

MAPK phosphorylation is implicated in the adaptation to desiccation stress in nematodes

Abstract: SUMMARYSome nematodes can survive almost complete desiccation by entering an ametabolic state called anhydrobiosis requiring the accumulation of protective molecules such as trehalose and LEA proteins. However, it is not known how anhydrobiotic organisms sense and regulate the response to water loss. Mitogen-activated protein kinases (MAPKs) are highly conserved signalling proteins that regulate adaptation to various stresses. Here, we first compared the anhydrobiotic potential of three nematode species, Caeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…All three types of MAPKs (ERK, p38 and JNK) play a role during desiccation, oxidative and osmotic stress in a wide range of organisms, regardless of whether they are able to reach an anhydrobiotic stage and survive severe desiccation conditions [63], [64], [65]. In F. heteroclitus mid-gastrula embryos, MAPKs may also be involved in the sensing and transduction of desiccation since we observed that expression of genes that can potentially participate in the p38 MAPK and SAPK/JNK ( dusp23-like , stk39 , mink1-like ), and MAPK/ERK ( prkcbb , camk2d ), signaling pathways is strongly and transiently enhanced after 30 min-1 h of aerial incubation (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three types of MAPKs (ERK, p38 and JNK) play a role during desiccation, oxidative and osmotic stress in a wide range of organisms, regardless of whether they are able to reach an anhydrobiotic stage and survive severe desiccation conditions [63], [64], [65]. In F. heteroclitus mid-gastrula embryos, MAPKs may also be involved in the sensing and transduction of desiccation since we observed that expression of genes that can potentially participate in the p38 MAPK and SAPK/JNK ( dusp23-like , stk39 , mink1-like ), and MAPK/ERK ( prkcbb , camk2d ), signaling pathways is strongly and transiently enhanced after 30 min-1 h of aerial incubation (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes are those potentially involved in phosphorylation signaling pathways, oxidative stress or molecular chaperones [5], [65], [105], suggesting critical adaptations to survival in killifish embryos that may resemble to other species undergoing dormancy, diapause or desiccation. Thus, desiccation resistance during delayed hatching of killifish embryos may be an useful model to elucidate common and distinct pathways for the long term preservation of animal cells.…”
Section: Resultsmentioning
confidence: 99%
“…Slow desiccated nematodes such as Aphelenchus avenae, require a period of slow desiccation as pretreatment before they survive in extreme dryness (Tunnacliffe and Lapinski, 2003). Rapid desiccated nematodes are capable to directly enter anhydrobiosis without pretreatment, for example Panagrolaimus superbus (Banton and Tunnacliffe, 2012). Diapausing C. elegans belong to the slow desiccated nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, to confirm the phosphorylation of p38MAPK by MKK3 in vivo , reversely increased activation of MKK3 is expected in response to inhibition of p38MAPK through negative feedback regulation [42], [43]. SB203580 is widely implicated as a specific inhibitor of p38MAPK [17], [44][46]. It binds to an extended pocket in the active site of p38MAPK and blocks the formation of functional complexes with substrates [47].…”
Section: Discussionmentioning
confidence: 99%